Native aluminum as indicator of hydrogen degassing in the formation of hydrocarbon fields - Lukin, A.; Koliabina, I.; Shestopalov, V.; Rud, A. (Geofizicheskiy Zhurnal, 2023)
This work considers the possibility of native aluminum transport with hydrogen fluid, its deposition and preservation in sedimentary rocks, as well as an assessment of the conditions under which this is possible. This problem is currently debatable and is considered in a number of publications. Native aluminum was found in different types of sedimentary rocks of oil-and-gas-bearing basins. So the presence of native aluminum spherulas was established in the dolomites of the Dnipro-Donetsk Basin. By the example of these findings this work shows that the necessary conditions for the formation and long-term preservation of native aluminum are: its migration with the hydrogen flow into the upper layers of the Earth’s crust, the creation of temperature and pressure conditions causing water to vaporize, and the formation of a protective film on the surface of the formed native aluminum. The process of native aluminum formation in the sedimentary rocks of oil-and-gas-bearing deposits of the Dnipro-Donetsk Rift described in this work, as well as its findings in other basins indicates the typical character of this process for rift structures of hydrocarbon accumulation. It was assumed, that the oil-and-gas-bearing structure of Dnipro-Donetsk Rift is mantle origin and represents a giant source of deep hydrogen. Some of this hydrogen is consumed to form hydrocarbon accumulations, including known oil and gas deposits, and some of it degasses into the uppermost layers of the Earth’s crust. Independent hydrogen fields can also form there, as was the case during the formation of the deposit of geological hydrogen in Mali. It was shown, that the presence of hydrocarbons in the fluids does not affect the processes associated with aluminum. The results obtained indicate significant flows of hydrogen from the mantle to the upper horizons of the Earth’s crust. Thus, native aluminum, as well as other native oxyphilic metals in sedimentary rocks of oil-and-gas bearing basins is a search marker of both hydrocarbon accumulations and the important role of deep geological hydrogen in the formation of these accumulations and its possible accumulation in the most reliable traps.